Ecophysiological attributes of Mikania micrantha, an exotic invasive weed, at two different elevations in the tropical forest regions of the Western Ghats, South India. Issue 1 (18th February 2014) - Prabu, N. Ramesh; Stalin, N.; Swamy, P. Sudhakar
<x xml:space="preserve">Abstract</x> Mikania micrantha H.B.K. is a fast‐growing, perennial vine and one of the world's worst alien invasive weeds. It is a major threat to agro‐ecosystems, plantation crops and agro‐forestry systems. An attempt was made to understand the physiological adaptation and ecological amplitude of M. micrantha at two different altitudes and seasons in the Western Ghats of south India. The relationships between the net photosynthetic rate (PN) and other physiological parameters, like stomatal conductance (gs), transpiration rate, intercellular CO2 concentration, vapor pressure deficit and water use efficiency, and environmental factors, like photosynthetically active radiation (PAR), leaf temperature and air temperature, were analyzed in order to understand their physiological adaptabilities. The PN exhibited a peak at 10.00 hours and declined gradually at both elevations; however, the populations at the lower elevation had a significantly greater PN than the populations at the higher elevation in November. The PN and gs were positively correlated with the PAR. Under significantly different PAR levels, the difference in the average PN was not significant for summer but was significant for winter between the two elevations. It suggested that the photosynthetic ability of M. micrantha is not affected by a difference in altitude (451 m and 912 m), as the differences in the environmental parameters were inconspicuous between the two elevations. These results indicated that this weed possesses great phenotypic plasticity and thrives better at lower elevations.